Effects of Absorption Kinetics on the Catabolism of Melatonin Released from CAP-Coated Mesoporous Silica Drug Delivery Vehicles - Irene Moroni; Alfonso E. Garcia-Bennett (MDPI AG, 2021)
Melatonin (MLT) is a pineal hormone involved in the regulation of the sleep/wake cycle. The efficacy of exogenous MLT for the treatment of circadian and sleep disorders is variable due to a strong liver metabolism effect. In this work, MLT is encapsulated in mesoporous silica (AMS-6) with a loading capacity of 28.8 wt%, and the mesopores are blocked using a coating of cellulose acetate phthalate (CAP) at 1:1 and 1:2 AMS-6/MLT:CAP ratios. The release kinetics of MLT from the formulations is studied in simulated gastrointestinal fluids. The permeability of the MLT released from the formulations and its 6-hydroxylation are studied in an in vitro model of the intestinal tract (Caco-2 cells monolayer). The release of MLT from AMS-6/MLT:CAP 1:2 is significantly delayed in acidic environments up to 40 min, while remaining unaffected in neutral environments. The presence of CAP decreases the absorption of melatonin and increases its catabolism into 6-hydroxylation by the cytochrome P450 enzyme CYP1A2. The simple confinement of melatonin into AMS-6 pores slightly affects the permeability and significantly decreases melatonin 6-hydroxylation. Measurable amounts of silicon in the basolateral side of the Caco-2 cell monolayer might suggest the dissolution of AMS-6 during the experiment.